2012
DOI: 10.6026/97320630008891
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and functional analysis of some snake venom toxin proteins and related non-toxin proteins of other chordates

Abstract: Snake venom contains a diverse array of proteins and polypeptides. Cytotoxins and short neurotoxins are non-enzymatic polypeptide components of snake venom. The three-dimensional structure of cytotoxin and short neurotoxin resembles a three finger appearance of three-finger protein super family. Different family members of three-finger protein super family are employed in diverse biological functions. In this work we analyzed the cytotoxin, short neurotoxin and related non-toxin proteins of other chordates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…For the translocation of BAX to mitochondria, a mitochondrial addressing signal of N-terminal Hα1 is believed to be necessary [29]. Recent bioinformatical research methods were very helpful for the discovery process of new biologically and biomedically important protein molecules [30][31][32][33][34][35][36][37][38][39]. Therefore, varied structural forms of BAX molecules in the different organisms (e.g., Chinese liver fluke) must be identified for bio-medical interventions.…”
Section: Resultsmentioning
confidence: 99%
“…For the translocation of BAX to mitochondria, a mitochondrial addressing signal of N-terminal Hα1 is believed to be necessary [29]. Recent bioinformatical research methods were very helpful for the discovery process of new biologically and biomedically important protein molecules [30][31][32][33][34][35][36][37][38][39]. Therefore, varied structural forms of BAX molecules in the different organisms (e.g., Chinese liver fluke) must be identified for bio-medical interventions.…”
Section: Resultsmentioning
confidence: 99%
“…It assesses analytically the volume as well as the area of each cavity and pocket, both in molecular surface (MS, Connolly's surface) and solvent accessible surface (SA, Richards' surface). It also measures the number of mouth openings, circumference of mouth lips, and area of the openings, in both SA and MS surfaces for each pocket [18]. …”
Section: Methodsmentioning
confidence: 99%
“…science, pharmaceutical science, and biological science [10][11][12][13][14][15][16][17]. In recent years, literatures have reported that hesperetin possesses the potential to behave as an effective inhibitor of thrombin-like serine proteases isolated from the venom of Crotalus simus snakes [18].…”
Section: Panda and Ehsanmentioning
confidence: 99%